(untitled) (Research, Society and Development, 2019)
Knowing the difficulties in Physics Teaching in the public schools of a city in the northern region of Brazil, we propose, in this research, a methodology of teaching through an interactive and experimental class with the contribution of meaningful learning. The main objective of this research is to make feasible the use of the proposed methodology considering the planning of the teacher when valuing the students’ view about this proposal. We apply this methodology when teaching sound waves classes in four classes of 3rd year of two public schools. During the research we carried out questionnaires before and after school to understand the opinion of the students about the local educational reality, if during the lessons there was learning and we also questioned if the methodology used in the classes was useful to facilitate the teaching-learning process. The results showed that the local educational reality needs to be reviewed so that the learning process occurs in a significant way, besides showing that there was learning during this research there was significant learning about the main topics of sound waves. Thus, the research showed the feasibility of using the methodology in schools that do not have advanced didactic resources.